Is this the Collapse of Islamic State? The Evolution of the Terrorist Threat in the Middle East in 2017 - WEJKSZNER, Artur (Przegląd Strategiczny, 2018)
The main aim of this article is to present an evolution of the terrorism threat in the Middle East in 2016. For this purpose, firstly, the essence and determinants of the contemporary terrorism threat have been analyzed. Some main Middle East terrorist organizations, actively operating in this area, have also been indicated. Secondly, the chronology and the most important terrorism trends in the region have been presented. A special attention has been paid to consequences of the fall of the Islamic State. And last but not least some predictive scenarios regarding the development of above phenomenon in 2017 and beyond have been pointed out.